Coastal environmental changes in Ninh Thuan Province, South-Central Vietnam. - Bijeesh Kozhikkodan Veettil; Siham Acharki; Vikram Puri; Vanna Teck (PLoS ONE, 2025)
Vietnam's coastal regions are highly vulnerable to natural hazards and human-induced changes, posing significant challenges to their ecological and socio-economic systems. The country's mangrove vegetation spans its entire coastline and has been depleted for decades in many regions. Notably, Vietnam's proactive stance on climate change mitigation received significant recognition during the 26th Conference of the Parties (COP26) to the United Nations Framework Convention on Climate Change. This study investigated five critical coastal environmental features (shoreline dynamics, drought conditions, soil salinity trends, mangrove deforestation, and reforestation, as well as spatiotemporal variations in aquaculture and salt farming areas) using satellite data and geospatial analysis. Findings revealed a 58% decline in mangrove areas between 1989 and 2023, with a sharp decline between 1989 and 2001, followed by a gradual recovery. Furthermore, soil salinity along the Ninh Thuan coast indicated a continuous increase, except during the strong La Niña period in 2001. Additionally, aquaculture and salt marshes have expanded significantly, changing land use patterns. These findings highlight the urgent need for integrated coastal zone management to mitigate environmental degradation and enhance ecosystem resilience. Future studies should investigate the socio-economic implications of these changes and evaluate restoration strategies for sustainable coastal development.